2014
DOI: 10.1530/eje-14-0397
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between glucocorticoid replacement and quality of life in 2737 hypopituitary patients

Abstract: Objective: Quality of life (QoL) is impaired in hypopituitary patients and patients with primary adrenal insufficiency. The aim of this study was to analyse the impact of glucocorticoid (GC) replacement on QoL. The main hypothesis was that ACTHinsufficient patients experience a dose-dependent deterioration in QoL. Design, patients and methods: This was a retrospective analysis of data from KIMS (Pfizer International Metabolic Database). Data from 2737 adult GH-deficient (GHD) hypopituitary patients were eligib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 42 publications
2
24
1
Order By: Relevance
“…In terms of quality of life, Ragnarsson et al showed in a retrospective cohort study of 2737 patients, that the quality of life index was lowest in patients with corticotroph deficiency treated with > 25 mg/day hydrocortisone and highest in patients treated with 10 mg/day [5]. This confirms the quality of life data reported in 2 prospective crossover studies on a total of 200 patients [21,22].…”
Section: Adult Patientssupporting
confidence: 52%
See 1 more Smart Citation
“…In terms of quality of life, Ragnarsson et al showed in a retrospective cohort study of 2737 patients, that the quality of life index was lowest in patients with corticotroph deficiency treated with > 25 mg/day hydrocortisone and highest in patients treated with 10 mg/day [5]. This confirms the quality of life data reported in 2 prospective crossover studies on a total of 200 patients [21,22].…”
Section: Adult Patientssupporting
confidence: 52%
“…There is no data presently to show if cortisone acetate, which undergoes conversion to cortisol through the action of 11beta-HSD-1 in the liver, is superior or inferior to hydrocortisone [3,4]. It should be noted that this enzyme is inhibited by the GH/IGF1 system, and could be theoretically less efficient in patients with a deficit in GH replacement, although this was not reported in a retrospective cohort study published by Ragnarsson et al [5]. Cortisone acetate is more readily accessible in some European countries, for example Italy [6].…”
Section: Adult Patientsmentioning
confidence: 96%
“…QoL is also impaired by the presence of postoperative ACTH insufficiency (25). Initial hydrocortisone treatment is followed by great symptomatic improvement, but chronic hydrocortisone substitution is shown to be associated with lower QoL, perhaps due to high, nonphysiological glucocorticoid doses (26).…”
Section: Hypopituitarism (Including Growth Hormone Deficiency)mentioning
confidence: 99%
“…In males, low testosterone is associated with physical impairment (i.e., reduced muscle strength or osteoporosis), as well as psychological disturbances (depression, anxiety and sexual dysfunctions like decreased libido), often associated to infertility which is another common complaint, all of which negatively impact on QoL (29). Using the generic SF-36 questionnaire, more problems in the areas of role-physical, vitality, physical functioning, general health and role-emotional were observed in hypogonadal patients when compared to healthy controls (25). After the replacement therapy with testosterone, vitality, physical role, general health and emotional role parameters improved, but were still below the reference values.…”
Section: Hypopituitarism (Including Growth Hormone Deficiency)mentioning
confidence: 99%
“…Similarly, too low doses can lead to fatigue and a higher frequency of adrenal crisis, deteriorating HRQoL (21). A recent retrospective cross-sectional study in SAI patients has found that higher HC doses were associated with worse HRQoL, and that patients with doses lower than 10 mg/day had the best HRQoL and patients receiving more than 25 mg/day the poorest HRQoL (22). Another study found that AI patients with doses higher than 30 mg/day have lower HRQoL levels than patients with lower doses (6).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%